TEKNOLOGI PENGAIRAN DAN PENGOLAHAN TANAH PADA BUDIDAYA PADI SAWAH UNTUK MITIGASI GAS METANA (CH4) - Naharia, Orbanus; Saeni, M Sri; Sabihan, Supiandi; Burhan, Harris (Research Center for Biology-Indonesian Institute of Sciences, 2005)
Global warming that caused by green house effect is one phenomena where short wave sunlight radiation penetrates the atmosphere and changes to become long wave on earth surface, when reaching the earth surface, a part of the wave reflected to atmmosphere,however not the entire reflected wave will be released to outer space; greenhouse gases layer in the atmosphere will reflect part of the wave to the earth surface resulting in increasing surface temperature.According to data from National Communication in 1997, agriculture and husbandry sectors give large contribution for the increasing green house gases particularly CH4 produced from rice field cultivation.Due to the reason, research for